Disdain for the body: Mysticism and Anthropology in Teresa of Ávila and John of the Cross - Cascante, Luis Diego (2026)
Between the 16th and 17th centuries, after the Council of Trent (1545-1563), the theological regulation mechanisms were joined to politics and made the body an ideologically objectionable space, so convents were the space for friars and nuns, acquire knowledge and, obliquely, develop an anthropology from religious life, but which becomes a spirituality (mystical) that leads to a parsimonious androgygy (in Teresa of Jesús and Juan de la Cruz) with respect to the human body and with respect to divinity, especially by characterizing relationships with divinity outside of the institutionalized conceptions of the Ecclesial Magisterium in relation to the roles of corporeality, in particular with contempt for the body.